Left atrial function assessed by speckle tracking echocardiography in anthracycline-induced cardiotoxicity: a case report. Issue 6 (12th November 2020) - Sueta, Daisuke; Usuku, Hiroki; Kinoshita, Yui; Tsujita, Kenichi
Abstract: Background: The onset prevention and early diagnosis in cardiotoxicity due to cancer chemotherapy are important, and it is important to detect cardiac dysfunction at an early stage and start treatment to enhance the therapeutic effect. Case summary: A 31-year-old female with breast cancer received chemotherapy with epirubicin (400 mg/m 2 ) and cyclophosphamide followed by docetaxel. Two months after the initiation of her chemotherapy, the left ventricular (LV) ejection fraction (LVEF) determined by echocardiography fell to 41.2%, and she was diagnosed with cancer therapy-related cardiac dysfunction (CTRCD). Three months after the initiation of cancer treatment, the peak velocity of late diastolic transmitral Doppler flow (A wave) became undetectable. Peak longitudinal strain (LS) and peak LS rate, which reflect left atrium (LA) reservoir function, gradually declined like the LVEF and LV-global LS (GLS). Seven months after the initiation of cancer treatment, she was diagnosed with acute decompensated heart failure. The changes in peak LS and peak LS at the onset were greater than those in LVEF and LV-GLS. Discussion: This is a case report suggesting that LA reservoir function might be a more sensitive indicator than LVEF or LV-GLS in detecting CTRCD and that LA booster function might be the earliest. Left atrium reservoir function might be a more sensitive than conventional LV pump function and optimal indicator in CTRCD.